The effect of nitrogen fertilization on growth, grain yield, and flag leaf characteristics of several Syrian soft wheat cultivars (Triticum aestivum L.) under the costal conditions - ديب آلاء; هزار حبيب; غياث علوش (Latakia University Journal -Biological Sciences Series, 2024)
A field experiment was conducted at the Sitkhears Research Station at Dibba site during the season 2021/2022. The aim was to study the response of soft wheat (Triticum aestivum) cultivars (Sham 4, Sham 6, Sham 8, and Sham 10) to different levels of nitrogen fertilizer. The experiment included four nitrogen levels (kg N/h-1: N0=0, N1=100, N2=200, N3=300) and three replications for each treatment, using a randomized complete block design within each cultivar (RCBD). The growth, productivity, and some leaf flag characteristics were investigated. The increased nitrogen fertilizer rates resulted in a significant increase in number of total tillers, and productive tillers in all cultivars, at the expense of non-productive tillers. The number of tillers reached approximately 4 tillers/plant at 300 kg N/h-1 nitrogen rate of application. The main stem and tillers heights showed a significant increase with nitrogen fertilizer rate of 100 kg N/h-1. However, increasing the nitrogen fertilizer rates to 200 and 300 kg N/h-1 did not lead to a significant increase in plant height. This was reflected in the straw yield, which reached 12.8 tons/h-1 at the nitrogen fertilizer rate of 300 kg N/h-1 for Sham 4 cultivar. Grain yield increased with increasing N application rate and reached 7736 and 7268 kg/h-1 for the Sham 4 and Sham 10 cultivars, respectively, at the 300 kg N/h-1 treatment. In comparison, the Sham 6 and Sham 8 cultivars had a grain productivity of 5215 and 5599 kg/h-1, respectively, at the same nitrogen level. The nitrogen additions had a highly significant effect on flag leaf characteristics, including leaf area, dry weight, and total chlorophyll concentration. Leaf area and dry weight increased significantly up to the nitrogen fertilizer level of 300 kg N/h-1, reaching their maximum values in the Sham 4 cultivar. Chlorophyll concentration continued to increase significantly up to the 200 kg N/h-1 rate, but there was no significant increase beyond that N application rate. The highest chlorophyll concentration was observed in the Sham 4 cultivar with the rate of 300 kg N/ha. Among the studied cultivars, Sham 4 showed the highest response to increasing nitrogen fertilizer rate.